2006
DOI: 10.1007/s10452-006-9055-1
|View full text |Cite
|
Sign up to set email alerts
|

The More the Merrier: Swarming as an Antipredator Strategy in the Mysid Neomysis Integer

Abstract: The swarming behaviour of a Baltic littoral mysid shrimp, Neomysis integer, was studied both in the presence and absence of a predator (European perch, Perca fluviatilis L.). I performed two kinds of laboratory experiments. First, the swarming tendency of mysids and the effect of swarm size on swarm choice were studied. Second, the ingestion rate of mysids was measured when feeding alone versus in a swarm. The results indicate that N. integer actively join swarms. The avoidance of the perch by N. integer indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The current study indicates that when placed in the broader community, the impacts of M. salemaai , as natives or invaders, may be somewhat ameliorated by higher predators through a combination of direct and non‐consumptive mechanisms, whereas the impacts of invasive H. anomala may be primarily ameliorated via direct mechanisms. As studies have indicated that predator avoidance behaviour in gregarious mysids is more pronounced in individuals than in groups (Lindén ), the ecological consequences of direct and non‐consumptive effects will primarily relate to the group level. Further, the risk‐foraging trade‐offs that result from predator avoidance can result in reduced growth and fecundity (Lima ), and M. salemaai is only capable of producing one brood per year, whereas H. anomala can produce up to four (Minchin & Boelens ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study indicates that when placed in the broader community, the impacts of M. salemaai , as natives or invaders, may be somewhat ameliorated by higher predators through a combination of direct and non‐consumptive mechanisms, whereas the impacts of invasive H. anomala may be primarily ameliorated via direct mechanisms. As studies have indicated that predator avoidance behaviour in gregarious mysids is more pronounced in individuals than in groups (Lindén ), the ecological consequences of direct and non‐consumptive effects will primarily relate to the group level. Further, the risk‐foraging trade‐offs that result from predator avoidance can result in reduced growth and fecundity (Lima ), and M. salemaai is only capable of producing one brood per year, whereas H. anomala can produce up to four (Minchin & Boelens ).…”
Section: Discussionmentioning
confidence: 99%
“…These mysids represent an ideal study system with which to explore higher order interactions as, generally, mysids are gregarious, group‐forming animals whose predatory efficacy is demonstrably related to their association with conspecifics (Hansson et al . ) which, in turn, can alter the non‐consumptive effects exerted by higher predators (Lindén ). More specifically, whilst congeners of M. salemaai have themselves been implicated as damaging invaders (Spencer, McCelland & Stanford ), H. anomala is also known to have severe ecological impacts (Ketelaars et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies on aggregation preferences in crustaceans ended up with complex results (e.g. Baumgärtner et al 2002;Evans et al 2007;Linden 2007). The present study suggests that the presence of predator cues may influence the tendency to aggregate in invertebrates and should be considered in examinations referring to this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that mysid species may be facilitative, whereby the formation of mixed species aggregations confers benefits to each of the component species. Such benefits may include, maintaining a suitable position in a favorable habitat (Clutter, 1969;Ritz, 1994), energetic benefits (Hough & Naylor, 1992;Herskin & Steffensen, 1998;Ritz, 2000), increased food uptake (Eggers, 1976;Ritz, 2000), reduced predation risk (Ritz, 1994;Lindén, 2007), and facilitation of breeding (Clutter, 1969;Ritz, 1994).…”
Section: Discussionmentioning
confidence: 99%